Organisasi Perempuan Salimah Kota Padang (2005-2023) - Melsi Fadhilla Fitri; Siti Fatimah (Jurnal Kronologi, 2026)
Many Islamic women's organizations have been established in Indonesia. Salimah (Persaudaraan Muslimah) is one of the Islamic women's organizations actively involved in women's empowerment. This research discusses the Salimah Women's Organization in Padang City from 2005 to 2023. This study utilizes historical research methods consisting of four stages: heuristics, source criticism, interpretation, and historiography. Data was obtained from Salimah's AD/ART, Salimah's GBHO, and photographic documentation. To obtain oral sources, interviews were conducted with the chair and secretary of Salimah Padang City, members, and the surrounding community.The results of this study indicate that the establishment of the Salimah organization in Padang City was motivated by the goal of strengthening Salimah's role not only at its headquarters in Jakarta but also in various regions across Indonesia's islands, including Sumatra, specifically West Sumatra, such as Padang. This was due to the limited preaching activities at that time. Furthermore, this research found that the Salimah organization in Padang City experienced dynamic development every year, particularly in its designed programs, ranging from the preaching field, such as Beranda Perempuan, the economic field, such as Saling Sapa, and the education field, such as MMC (Muslimah Milineal Community) and the storytelling workshop (Workshop Berkisah). Through these programs, it is hoped that a positive impact on the surrounding community will be achieved.